2020
DOI: 10.1108/maj-01-2019-2136
|View full text |Cite
|
Sign up to set email alerts
|

Can internal audit functions improve firm operational efficiency? Evidence from China

Abstract: Purpose The purpose of this study is to examine the effects of internal audit function (IAF) quality on the operational efficiency of Chinese firms. Design/methodology/approach The authors use regression models with a sample of Chinese listed companies to test their research hypotheses. Findings The authors find that IAF quality is positively associated with firm operational efficiency. The result is unchanged after correcting for endogeneity via the instrumental variable method and using an alternative me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…This remarkable finding is consistent with Ege (2015), who has found that IAF competence, but not objectivity, is negatively associated with the likelihood of management misconduct, suggesting that IAF competence is vital in preventing management misconduct. It is also consistent with Chen et al (2020), Kaawaase et al (2021) and Oussii and Boulila Taktak (2018), who indicated a significant result for IAF competence but not for IAF independence. Competent IAF is more able to deter fraud, earnings management or irregularities.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This remarkable finding is consistent with Ege (2015), who has found that IAF competence, but not objectivity, is negatively associated with the likelihood of management misconduct, suggesting that IAF competence is vital in preventing management misconduct. It is also consistent with Chen et al (2020), Kaawaase et al (2021) and Oussii and Boulila Taktak (2018), who indicated a significant result for IAF competence but not for IAF independence. Competent IAF is more able to deter fraud, earnings management or irregularities.…”
Section: Resultssupporting
confidence: 89%
“…Also, Asiedu and Deffor (2017) concluded that the size (as a proxy of competence) and independence significantly affect the effectiveness of the IAF in fighting administrative corruption in Ghana. On the other hand, some studies provide evidence that supports the positive association between IAF competence and firm operational efficiency (Chen et al , 2020), internal control quality (Oussii and Boulila Taktak, 2018) and financial reporting quality in financial institutions (Kaawaase et al , 2021), whilst they found no evidence that supports such association with IAF independence. In addition, Morais and Franco (2019) surveyed external auditors in Portugal and found that competence is most important for external auditors to trust and cooperate with internal auditors.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 98%
“…In addition, auditing ensures transparency and minimises information asymmetry, thereby ensuring higher investment efficiency. Similarly, Chen et al (2020) posit that firms' internal audit functions improve operational efficiency. They note that the internal control mechanisms influence the operational efficiency of Chinese listed companies.…”
Section: Related Literaturementioning
confidence: 99%
“…We have identified the most suggested topics from the latest articles, which we think need to be investigated better and broadly; (1) Conducting studies to research the role of executive management in foreign institutions in enhancing the performance of the IA role and comparing them with the results obtained in this study so that those interested can know the differences in light of the lack of complete disclosure of information in Chinese institutions (Zeng et al, 2020). (2) Conducting studies to know the lenders' vision and perceptions of the efficiency of the IA function by examining the terms of debt contracting, researching whether the quality of the IA functions improves the efficiency of investment, and exploring the importance of the efficiency of IA functions in improving operational processes in new and emerging economies under a system that differs from the system used in Chinese institutions to find out the differences, which contribute to the development of internal audit (Chen et al, 2020); (3) Carrying comparative studies using samples from other countries with a government system that differs from the socialist system followed in China, in addition to taking into account the difference in the culture of the country in which the study is being conducted from the culture of China to examine the vocal behaviour of the auditors in all fields, including governance issues and issues related to the social environment (Liu et al, 2020). Finally, further work could evaluate the impact of Covid-19 on IA function.…”
Section: Direction Using Suggestions From the Latest Research Articlesmentioning
confidence: 99%